Hydrocolloids for Tissue Engineering and 3d Bioprinting - Yildirim-Semerci, Ozum; Arslan Yıldız, Ahu; Onbas, Rabia; Bilginer-Kartal, Rumeysa; Arslan-Yildiz, Ahu (World Scientific Publ Co Pte Ltd, 2024)
Hydrocolloids, derived from plants, marine, and microbial sources, have become research favorites due to their unique properties. This article provides an overview of the extraction methods, from chemical to enzymatic, to obtain hydrocolloids. Distinctive properties of hydrocolloids, such as high swelling capacity, tunable features, and rapid gelation ability, have gained significant attention recently and have started to be used in tissue engineering and 3D bioprinting. Hydrocolloids will play substantial roles in advancing biomedical products and contributing to improving human health.
Hydrocolloids for Tissue Engineering and 3D Bioprinting
Arslan Yildiz, Ahu/0000-0003-0348-0575; Yildirim-Semerci, Ozum/0000-0001-7203-3870
Keywords: Hydrocolloids; 3D Bioprinting; Tissue Engineering